Marketing : a guide to the fundamentals - Forsyth, Patrick (New York, 2009)
For anyone who wants to understand the marketing mix, the factors involved in pricing policy, the different methods of market research, indeed the whole business of marketing; this guide to the fundamentals will be invaluable
Keywords: Marketing